Avaliação de arranjos supramoleculares de complexos triazenidos de mercúrio (II) e cobre(II) - Koehler, Eduardo Giuliani (2007)
The reaction between deprotonated 1,3-Bis(3-acetylphenyl)triazene and Hg(CH3COO)2 in methanol, yields [Hg(RNNNR)(Py)] (R=3-CH3C(O)C6H4) (1), a triazenide dimeric mononuclear complex of mercury(II). The crystal structure analysis of (1) reveals a bi−dimensional supramolecular arrangement as result of molecular self-assembly provided by Hg−η², η² −arene π interactions, and C−H···O non−classical hydrogen bonding. The crystal system of (1) is monoclinic and belongs to the space group P21/c with the cell parameters a = 13,8647(5), b = 14,8823(5), c = 17,0403(5) Å, and β = 92,2140(10)°. The crystal structure refinement achieves the final indexes R1 = 0,0440 and wR2 = 0,1034. Deprotonated 1,3-Bis(3-acetylphenyl)triazene reacts with Cu(CH3COO)2·2H2O in methanol yielding [Cu(RNNNR)2]2 (R = 3−CH3C(O)C6H4) (2), a binuclear triazenide complex showing a lantern −type molecular structure. The crystal structure of (2) reveals that molecules of the complex do not suffer intermolecular interactions. The Cu···Cu distance [2,4056(9)Å] give rise to the interpretation of an inter-metallic interaction supported by an anti−ferromagnetic coupling between the Cu(II) ions. The crystal system of (2) is triclinic and belongs to the space group P(-1) with the cell parameters a = 10,1977(11), b = 15,5390(19), c = 19,173(2) Å, α = 92,960(3)°, β = 90,484(4)°, and у = 100,997(3)°. The crystal structure refinement achieves the final indexes R1 = 0,0572 and wR2 = 0,1197. Beside the single−crystal X−ray structural analysis, both the complexes of (1) and (2) were characterized by infra-red vibrational spectroscopy and UV/VIS electronic transition spectroscopy.